Implementation of Bureaucratic Reform in Realizing the Title of Integrity Zone Towards A Corruption-Free Area and A Clean Bureaucratic Area at PDAM Tirta Langkisau of Pesisir Selatan Regency - Sakila, Dista; Khaidir, Afriva (Journal of Governance and Social Policy, 2024)
Bureaucratic reform is important to create a Corruption-Free Region and a Clean Serving Bureaucratic Area that is clean, accountable, and performant. This study uses a descriptive qualitative approach with interview and documentation methods, as well as analyzing data through reduction, presentation, and conclusion drawn. The focus is on the implementation of 6 Areas of Change in the development of the Integrity Zone. The findings show that PDAM Tirta Langkisau has carried out bureaucratic reforms well, although it still faces problems such as customer account arrears, placement of employees who do not match their educational background, and lack of socialization of the SIPDAM application. This problem requires the attention of PDAM and the government to support the creation of WBK and WBBM in PDAM Tirta Langkisau.